2016
DOI: 10.1002/zaac.201600263
|View full text |Cite
|
Sign up to set email alerts
|

A Sterically Encumbered 13/15 Cycle and its Cleavage with N‐heterocyclic Carbenes and other Lewis Bases

Abstract: Herein, the latest results on the topic of NHC-stabilized, monomeric group 13 metalsilylphosphanides, with the focus on the sterically demanding [GatBu 2 R x ]-fragment (x = 1, 2) are presented. The synthesis and characteristics of the cyclic compound [tBu 2 GaP(H)SitBuPh 2 ] 2 (1), followed by the cleavage of this cycle with different Lewis bases like pyridine, DMAP or the IiPr carbene is described for the first time. The compounds * Prof. Dr. C. von Hänisch

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A series of NHC-stabilized monomeric group 13 metalsilylphosphanides [(NHC)R 2 M−P(H)Si t BuPh 2 ] 422, 423 (Figure 46) were achieved through the cleavage of the fourmembered cyclic compounds [R 2 M−P(H)Si t BuPh 2 ] 2 (M = Al, Ga, In) upon treatment with NHCs. 423,424 The solid-state structure of 422 revealed a cis-orientation of the NHC and the silyl group relative to the M−P bond axis, while a trans-orientation was found for complexes 423a−d. 46).…”
Section: Nhc Adducts Of Aluminum In Low Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of NHC-stabilized monomeric group 13 metalsilylphosphanides [(NHC)R 2 M−P(H)Si t BuPh 2 ] 422, 423 (Figure 46) were achieved through the cleavage of the fourmembered cyclic compounds [R 2 M−P(H)Si t BuPh 2 ] 2 (M = Al, Ga, In) upon treatment with NHCs. 423,424 The solid-state structure of 422 revealed a cis-orientation of the NHC and the silyl group relative to the M−P bond axis, while a trans-orientation was found for complexes 423a−d. 46).…”
Section: Nhc Adducts Of Aluminum In Low Oxidationmentioning
confidence: 99%
“…A series of NHC-stabilized monomeric group 13 metalsilylphosphanides [(NHC)­R 2 M–P­(H)­Si t BuPh 2 ] 422 , 423 (Figure ) were achieved through the cleavage of the four-membered cyclic compounds [R 2 M–P­(H)­Si t BuPh 2 ] 2 (M = Al, Ga, In) upon treatment with NHCs. , …”
Section: Nhc Complexes Of Main Group Elementsmentioning
confidence: 99%
“…The bond lengths of Ga–Cl and Ga–N are 2.2293(10) and 2.013(3) Å, respectively. These lengths are comparable to those observed in the usual terminal Ga–Cl single bonds (2.22–2.29 Å) and the nitrogen to gallium coordination bonds (2.01–2.08 Å). , The CC and C–C bond lengths within the GaC 4 ring are 1.343(5)–1.349(4) and 1.529(5) Å, respectively, which are within the ranges in those reported for Lewis-base coordinated gallole derivatives (1.34–1.36 and 1.51–1.53 Å, respectively). , …”
Section: Resultsmentioning
confidence: 99%
“…However, when the substituents on Ga are bulkier, they observed that using a strong σ‐donor Lewis base is not enough to cleave the oligomeric heterocycle when the steric demand is high. Thus, pyridine, DMAP and IPr (1,3‐di iso propyl‐4,5‐dimethylimidazole‐2‐ylidene) can coordinate ( IV ) [10c] . Only IMes and IDip can provide such stabilization after a rearrangement if the group at the phosphorous terminal is large ( V ) [10a] …”
Section: Introductionmentioning
confidence: 99%